Analisis Kontribusi Pajak Hotel Dalam Meningkatkan Pendapatan Asli Daerah Kota Medan - Agus Verawati Tamba; Emi Masyitah (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
This type of research is descriptive qualitative, using primary and secondary data obtained from the Medan City BAPENDA and results from interviews with Bapenda employees and hotel taxpayers. The data management was assisted by the NVivo 12 Plus application. The results of the study show that the contribution of hotel tax to PAD in Medan City is categorized as good, but not optimal. Some identified obstacles include (a) low taxpayer awareness in paying on time, (b) lack of supervision over tax reporting, (c) the impact of the pandemic on hotel occupancy rates, and (d) limitations in the digitalization of reporting and payment systems. The strategy implemented by Bapenda includes sending warning letters and bills to taxpayers at the beginning of the month, as well as conducting direct field supervision. On the other hand, hotel operators hope that the tax system can be more practical, flexible, and support business sustainability, especially for small-scale hotels. Collaboration between the local government and business operators is key to enhancing the effectiveness of hotel tax revenue and supporting sustainable regional development.